The Effect of Service Quality, E-WOM, and Patient Satisfaction on Revisit Intention Moderated by Health Consciousness at Wonokusumo Public Health Center - Retno, Citra Widya; Rachmat, Basuki (JURNAL MANAJEMEN MOTIVASI, 2025)
This study aims to analyse the effect of service quality, electronic word of mouth (e-WOM), and patient satisfaction on patient revisit intentions at Wonokusumo Public Health Centre, with health consciousness as a moderating variable. Despite its strategic role in promoting public health, patient visits have not significantly increased despite service innovations. Using a quantitative approach and a sample of 252 respondents. The results of this study indicate that service quality significantly affects patient revisit intention, patient satisfaction, and electronic word of mouth (e-WOM). However, patient satisfaction and e-WOM do not considerably affect revisit intention, and health consciousness does not moderate the relationship between satisfaction and e-WOM. This study suggests that Wonokusumo Health Center are expected to focus on improving service quality dimensions to strengthen patient satisfaction and indirectly enhance revisit intention. Furthermore, future studies should explore alternative moderating factors influencing the relationship between satisfaction and patient behaviour. This study suggests that Wonokusumo Health Center is expected to focus on improving service quality dimensions to strengthen patient satisfaction and indirectly enhance revisit intention